Evaluasi Kompetensi Pedagogik Guru Kimia Dalam Menyusun Instrumen Penilaian Higher Order Thinking Skill (HOTS) Siswa SMA - Andromeda Andromeda; Zonalia Fitriza; Faizah Qurrata 'Aini (Edukimia, 2020)
Basic Competence (BC) is a minimum students’ achievement after learning process. Most of the BC in the 2017 revised Indonesian curriculum requires students to have higher order thinking skills (HOTS), therefore teachers have to prepare assessment instruments referring HOTS. However, there are still many teachers who misperceive HOTS and think that HOTS is a difficult problem. This causes the teacher’s understanding of HOTS questions to be low. This study aims to describe chemistry teachers’ competence in evaluating HOTS of students. 19 teachers from 14 Senior High Schools was examined using structured essay test to figure out their ability and problems in compiling HOTS assessment instrument. The data collected was analysed using Miles Huberman methods starting with data reduction, data display and conclusion. Through this evaluation, it is known that only 10.53% of teachers comprehended HOTS and were able to apply it in evaluation, 57,89% of them understood the HOTS but weren’t able to apply in evaluation while 31,58% others didn’t know the comprehensive HOTS evaluation. This fact will certainly disrupt the planning, implementation and assessment of learning. Furthermore, the instrument compiled to assess higher order thinking skills based on BC does not measure expected abilities.